A revision of chestnut-leaved oak (Quercus castaneifolia C. A. Mey.; Fagaceae) in Hyrcanian Forests of Iran - Panahi, P. (Caspian Journal of Environmental Sciences, 2011)
Chestnut-leaved oak (Quercus castaneifolia C. A. Mey) is one of the most important native oaks of Iran distributed in the Hyrcanian Forests. The pure and mixed stands of it cover about 6.5% of these forests. The species represents morphological variations which have resulted in the description of several infraspecific taxa by different authors. Eight taxa were recognized as subspecies and varieties of Q. castaneifolia. In this survey, a set of quantitative and qualitative micro-morphological characteristics such as type of trichome, number and length of trichome rays, type of epicuticular waxes, type and shape of stomata, shape and sculptural features of pollen exine were studied using light microscopy and scanning electron microscopy. These characters were analyzed by the discriminant analysis method and combined with the macromorphological characters to designate the variation within the species and to evaluate the existing infraspecific taxa. Based on our results, the studied taxa are defined into four infraspecific taxa as follows: Q. castaneifolia subsp. castaneifolia var. castaneifolia, Q. castaneifolia subsp. castaneifolia var. minuta, Q. castaneifolia subsp. aitchisoniana, Q. castaneifolia subsp. undulate. The studied characteristics showed to be diagnostic for identification of the infraspecific taxa.